2015
DOI: 10.1007/s12576-015-0386-3
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia in human and experimental animal models: physiological aspects related to neuropeptides

Abstract: Anorexia, a loss of appetite for food, can be caused by various physiological and pathophysiological conditions. In this review, firstly, clinical aspects of anorexia nervosa are summarized in brief. Secondly, hypothalamic neuropeptides responsible for feeding regulation in each hypothalamic nucleus are discussed. Finally, three different types of anorexigenic animal models; dehydration-induced anorexia, cisplatin-induced anorexia and cancer anorexia-cachexia, are introduced. In conclusion, hypothalamic neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 132 publications
(153 reference statements)
1
10
0
Order By: Relevance
“…The results of our study as well as previous studies demonstrated that both central and peripheral administration of ghrelin induced Fos expression in various regions, including the hypothalamic nuclei [6, 21]. The hypothalamic nuclei are important sites that regulate feeding and energy metabolism [6, 21, 2730]. The neurons located in the PVN, the Arc, and the LHA express GHSR [6, 21].…”
Section: Discussionsupporting
confidence: 79%
“…The results of our study as well as previous studies demonstrated that both central and peripheral administration of ghrelin induced Fos expression in various regions, including the hypothalamic nuclei [6, 21]. The hypothalamic nuclei are important sites that regulate feeding and energy metabolism [6, 21, 2730]. The neurons located in the PVN, the Arc, and the LHA express GHSR [6, 21].…”
Section: Discussionsupporting
confidence: 79%
“…In anorexia nervosa, the suppression of appetite is because of the psychiatric need to adjust body image to unrealistic models . In fact, a part of patients suffering from anorexia nervosa may not lack appetite . In secondary anorexia, the suppression of the appetite is because of the function disruption of the neuronal pathways that regulate the physiological eating behaviour …”
Section: Anorexiamentioning
confidence: 99%
“…Anorexia nervosa is thought to be triggered by a combination of multiple biological and social factors . This condition is closely related to social pressure and media exposure and is not easy to treat …”
Section: Anorexiamentioning
confidence: 99%
“…Currently, there are numerous presumptions that postulate the existence of a relationship between anxiety/AN pathogenesis and disturbances in brain peptidergic circuits (Cuesto et al 2017, Gorwood et al 2016, Yoshimura et al 2015. Despite the accumulating number of neurochemical studies, there is still insufficient evidence dealing with the influence of central peptidergic signaling on the course of anxiety and eating disorders.…”
Section: Introductionmentioning
confidence: 99%